Pengembangan Media Boardgame “Jelajah Nusantara” Berbasis Canva Interaktif untuk Meningkatkan Hasil Belajar Pendidikan Pancasila pada Materi Menjaga Keberagaman Budaya dan Agama - Ramadhani, Dini Ashri; Junaedi, Akhmad (Paedagogie, 2026)
This study developed and evaluated the effectiveness of an interactive board game learning medium titled "Jelajah Nusantara" designed using the Canva platform. The medium was intended to enhance elementary students' learning achievements on the topic of appreciation for cultural and religious diversity within the Pancasila Education curriculum. The research employed a Research and Development (R&D) approach adapted from a simplified Borg and Gall framework. The study involved 28 sixth-grade students from SDN Wates 01 Semarang as research subjects. Data collection techniques included field observations, in-depth interviews, questionnaires, and learning assessments through pre-tests and post-tests. Data analysis focused on comparing pre-test and post-test scores to measure students' learning progress and achievement of mastery standards. Pre-test results showed a mean score of 61.07, with only 3 out of 28 students (10.71%) meeting the minimum mastery criteria. Following the implementation of the "Jelajah Nusantara" board game, the post-test mean score increased to 74.64, with 9 students (32.14%) achieving mastery. These data indicate a significant improvement in learning achievement, marked by a 42.86 percentage point increase in the mastery rate. The research findings confirm that the Canva-based interactive board game "Jelajah Nusantara" is effective as an instructional medium for Pancasila Education, particularly in strengthening elementary students' understanding of cultural and religious pluralism in Indonesia.